The role of the cerebellum in sequencing and predicting social and non-social events in patients with bipolar disorder - Siciliano, Libera; Olivito, Giusy; Lupo, Michela; Urbini, Nicole; Gragnani, Andrea; Saettoni, Marco; Delle Chiaie, Roberto; Leggio, Maria (Frontiers in Cellular Neuroscience, 2023)
Advances in the operational mode of the cerebellum indicate a role in sequencing and predicting nonsocial and social events, crucial for individuals to optimize high-order functions, such as Theory of Mind (ToM). ToM deficits have been described in patients with remitted bipolar disorders (BD). The literature on BD patients’ pathophysiology reports cerebellar alterations; however, sequential abilities have never been investigated and no study has previously focused on prediction abilities, which are needed to properly interpret events and to adapt to changes. To address this gap, we compared the performance of BD patients in the euthymic phase with healthy controls using two tests that require predictive processing: a ToM test that require implicit sequential processing and a test that explicitly assesses sequential abilities in non-ToM functions. Additionally, patterns of cerebellar gray matter (GM) alterations were compared between BD patients and controls using voxel-based morphometry. Impaired ToM and sequential skills were detected in BD patients, specifically when tasks required a greater predictive load. Behavioral performances might be consistent with patterns of GM reduction in cerebellar lobules Crus I-II, which are involved in advanced human functions. These results highlight the importance of deepening the cerebellar role in sequential and prediction abilities in patients with BD.